Simulation of Competitive Activities of Skaters in Short-Track - Kholodova, O.; Shemchuk, V.; Trachuk, S.; Semenenko, V.; Brychuk, M.; Pidoprygora, M. (Teorija i metodika fizichnogo vihovannja, 2023)
Modeling of competitive activity forms the basis for the rationalization and improvement of those means and methods that are used in sports training of athletes. In this regard, a hypothesis was put forward that predictive skating models will ensure the achievement of a certain level of sports results in short-track speed skating.